TREM2 Alzheimer's variant R47H causes similar transcriptional dysregulation to TREM2 knockout in human IPSC‐derived macrophages: Developing topics. (7th December 2020) - Roberts, Hazel Hall; Agarwal, Devika; Daniel, Elena Di; Webber, Caleb; James, William S; Mead, Emma; Davis, John B; Cowley, Sally A
Abstract: Background: TREM2 is a microglia‐specific gene, with mutations linked to Alzheimer's disease, including R47H (1). In AD mouse models, knockout (KO) of TREM2 impairs microglial clustering around amyloid and prevents microglia from being activated into a "disease‐associated" transcriptional state (2). The R47H mutation has been proposed to reduce ligand binding and therefore reduce TREM2 function (3). Method: We generated primitive macrophages from human induced pluripotent stem cell (iPSC) harbouring isogenic R47H TREM2 and TREM2 KO mutations gene‐edited onto a healthy genetic background, as a practical, simple model of human microglia. We performed bulk RNA‐seq and compared significant differentially‐expressed genes (DEGs: FDR corrected p<0.05) between the R47H and KO versus WT. Selected hits were validated by qPCR, flow cytometry and western blotting. We also used a bioinformatics approach to predict potential upstream regulators of sets of DEGs. Result: TREM2 KO resulted in a transcriptional signature hallmarked by dysregulation of genes involved with immune processes, calcium homeostasis, cell cycle, cell activation and chemotaxis. Although 3‐fold fewer DEGs were identified for R47H TREM2, 90% of these were also dysregulated in the KO, with directionality preserved. Validation confirmed specific defects in integrin expression in the R47H and KO. A candidate upstream regulator from the bioinformatics analysis was explored in cell assays, to shed more light on the underlying molecular mechanisms linking TREM2 KO to changes in adhesion and motility. Conclusion: The overlap in transcriptional defects between R47H TREM2 and KO (with R47H intermediate between WT and KO) supports the hypothesised partial loss‐of‐function effects of this mutation in humans. Guerriero et. al. (2013) N Engl J Med. 368 (2):117‐27. Krasemann et al. (2017) Immunity 47, 566–581. Kober et al. (2016). eLife, 5, e20391.